Do Classes of Polysubstance Use in Adolescence Differentiate Growth in Substances Used in the Transition to Young Adulthood?. (10th November 2018) - Merrin, Gabriel J.; Leadbeater, Bonnie
ABSTRACT: Background: Past studies have differentiated classes of polysubstance use in adolescence, however, the associations of adolescent polysubstance use classes with longitudinal substance use trajectories from adolescence to young adulthood have not been studied. Objective: The current study examined substance use classes during adolescence and longitudinal trajectories of each substance used across the transition to young adulthood. Method: Data were collected biennially from 662 youth and followed 10 years across six measurement assessments. Using baseline data (T1), latent class analysis was used to identify classes of polysubstance use (cigarette, alcohol, marijuana, and illicit drug use) during adolescence. Using T2 through T6 data, we fit latent growth models for cigarette, alcohol, marijuana, and illicit drug use to examine longitudinal trajectories of each substance used by class. Results: A three-class model fit the data best and included a poly-use class, that had high probabilities of use among all substances, a co-use class, that had high probabilities of use among alcohol and marijuana, and a low-use class that had low probabilities of use among all substances. We then examined trajectories of each substance used by class. Strong continuity of substance use was found by class across 14 years. Additionally, for some substances, higher average levels of use of at age 14 were associated with change in growth of other substances used over time. Conclusions/Importance: Efforts that only target a single drug type may be missing an important opportunity to reduce the use and subsequent consequences related to the use of multiple substances.